Post-splenectomy Posterior Reversible Encephalopathy Syndrome in a β-Thalassemia Major child with Evans Syndrome (GAIMS Journal of Medical Sciences, 2023)
Patients with β-Thalassemia Major are at risk of alloimmunization and autoimmunization because they need regular multiple blood transfusions. Here we are reporting a case of an 8 years old male child, known case of β-thalassemia major, who developed autoimmune pancytopenia, known as Evans syndrome, and post-splenectomy neurological complication Posterior Reversible Encephalopathy Syndrome (PRES). Evans syndrome (ES) is a rare autoimmune disorder characterized by autoimmune hemolytic anemia (AIHA) and immune thrombocytopenia (ITP) with or without immune neutropenia. There is no established evidence-based treatment. Steroids are used as a first-line therapy. Intravenous immunoglobulin is used as a life-saving therapy in severe cases. Rituximab and splenectomy are used as a second-line therapy. PRES is linked with hypertension. Characteristic clinical features of PRES are headache, blurring of vision, seizures, altered consciousness, cortical blindness or transient motor deficit.